The American Society for Clinical Pathology's 2016-2017 Vacancy Survey of Medical Laboratories in the United States. Issue 5 (7th March 2018) - Garcia, Edna; Kundu, Iman; Ali, Asma; Soles, Ryan
Abstract: Objectives: To determine the extent and distribution of workforce shortages within the nation's medical laboratories. Methods: The 2016-2017 Vacancy Survey was conducted through collaboration between the American Society for Clinical Pathology's Institute of Science, Technology, & Policy in Washington, DC, and the Evaluation, Measurement, and Assessment division and Board of Certification in Chicago, Illinois. Data were collected via an internet survey that was distributed to individuals who were able to report on staffing and certifications for their laboratories. Results: Results of the 2016-2017 Vacancy Survey shows decreased vacancy rates for laboratory positions across all departments surveyed compared with 2014. While overall, the data show that vacancy rates are decreasing, overall retirement rates and certification requirements are higher. Conclusions: Focus on the qualifications and certification status of laboratory professionals would be crucial factors in addressing the needs of the laboratory workforce. The field needs to intensify its efforts on recruiting the next generation of laboratory personnel.